The Eve of Global Conflict or Contra Spem Spero? - O. V. Gaman-Golutvina (Сравнительная политика, 2024)
The article contains the description of the world political context that influences the evolution of the military-political sphere. The articles of the presented issue are devoted to this analysis. As a methodological framework, it is proposed to use the information introduced into scientific circulation by J. Rosenau in 1990, the concept of turbulence in world politics, which was developed in later literature. For an adequate interpretation of current trends in military policy, it is proposed to take into account the differences between modern conflicts and wars from their previous forms. In particular, it is appropriate to take into account the differences between total and limited wars established in the literature earlier. Another conceptual characteristic of modern wars is the theory of "world war" formulated in the doctrinal documents of the United States, in which military conflicts and their borders become indistinct, while the opposing sides include both military units and irregular formations. It is noted that for Russia, the security problem is historically a key problem, which is determined by the geopolitical location of an extended land state. The influence of this geopolitical circumstance was reflected in the configuration of Russian statehood with its traditional emphasis on a rigid hierarchy of governance, a strictly vertical decision-making algorithm and the centralization of the territorial structure, as a result of which hierarchization was not just an attribute of the historical evolution of Russia, but an archetypal form of organization of the country’s political space. In the modern world, the matrix of social organization is changing: a network appears next to the hierarchy, which problematizes the lack of alternative hierarchical decision-making algorithm and actualizes the updating of security concepts.